Reflex sympathetic dystrophy arising in a patient with hemophilia A - Akarsu, Saadet; Taşkin, Erdal; Yilmaz, Erdal; Varol, F. Ilknur; Aygün, A. Denizmen; Özercan, Ibrahim H. (My University, 2005)
Reflex sympathetic dystrophy syndrome (RSDS) is characterized by severe pain, swelling and autonomic dysfunction of the affected extremity. Major or minor trauma is the most common initiating factor. Pain in the affected extremity is usually associated with vasomotor and sudomotor changes. We report an interesting case of RSDS of the right knee joint of a 10-years old boy with symptoms persisting more than one year and burning pain refractory to the treatments for hemophilic hemarthrosis. After his last hemarthrosis attack, his burning pain was protracted. Approximately two months after this diagnosis, a unilateral hyperthrichosis was revealed at the right upper leg also invading the knee. This is a case of RSDS with predominant cutaneous involvement. As for as we know, there is no previously reported case of RSDS after hemophilic hemarthrosis. To our knowledge, this is the first reported case of RSDS arising in a patient with hemophilia A.
Hemofili A olan hastada refleks sempatik distrofi sendromu
Keywords: Arthritis; Hemophilia; Reflex sympathetic dystrophy syndrome